2018
DOI: 10.19044/esj.2018.v14n1p240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Government Debt on Economic Growth in Kenya: A Critical Literature Review

Abstract: The study examined the impact of government debt on economic growth through extensive review of relevant theoretical and empirical literature. Governments borrow to cover budget deficits. The debt is obtained either from the domestic market or from external sources. Government debt by Greece proved to be bad for the economy while government debt by USA which has the highest debt in the world proved to be manageable. This led to the need to examine the impact of government debt on economic growth in Kenya. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Looking at the recent literature, these studies still contradict each other, as the study by Pekgas (2018) finds that public debt is negatively related to economic growth after a certain threshold in the case of Greece. Murungi and Okiro (2018) find the existence of a linear relationship between government debt and economic growth. A strong contradiction emerged from the study by Saungweme and Odhiambo (2019), as they reported that the relationship between public debt and economic growth in Zambia for the period from 1970 to 2017 is clear-cut.…”
Section: Empirical Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…Looking at the recent literature, these studies still contradict each other, as the study by Pekgas (2018) finds that public debt is negatively related to economic growth after a certain threshold in the case of Greece. Murungi and Okiro (2018) find the existence of a linear relationship between government debt and economic growth. A strong contradiction emerged from the study by Saungweme and Odhiambo (2019), as they reported that the relationship between public debt and economic growth in Zambia for the period from 1970 to 2017 is clear-cut.…”
Section: Empirical Literaturementioning
confidence: 93%
“…The first strand is those studies that believed in the neoclassical theory, arguing that government debt is detrimental to growth (Checherita-Westphal and Rother, 2012;Alves, 2014;Swamy, 2015;Pegkas, 2018;Asteriou et al, 2021). While the second strand believed in the endogenous growth model, claiming that government debt promotes economic growth (Spilioti and Vamvoukas, 2015;Burhanudin et al, 2017;Jacobo and Jalile, 2017;Yang et al, 2022;Ale et al, 2023;Abille and Kiliç, 2023), The last strand believed in those studies that believe that government debt and economic growth are characterized by a nonlinear relationship in nature (Elbadawi et al, 1997;Pattillo et al, 2004;Perlo-Freeman and Webber, 2009;Kremer et al, 2013;Seletenget et al, 2013;Akhanolu et al, 2018;Seletenget et al, 2013;Alam et al, 2019;Murungi and Okiro, 2018;Mensah et al, 2019;Ndoricimpa, 2020;Makhoba et al, 2022aMakhoba et al, , 2022bMqolombeni et al, 2023;Augustine and Rafi, 2023); even among those studies on NRN, there are contradicting results, as some studies find the invented U-shape (Perlo-Freeman and Webber, 2009;Kremer et al, 2013;Seletenget et al, 2013;Ndoricimpa, 2020;Makhoba et al, 2022aMakhoba et al, , 2022bAugustine and Rafi, 2023;Mqolombeni et al, 2023), while others find the U-shape relationship. While others Public debt and economic growth believed that there is no clear relationship between government debt and economic growth (Ferreira, 2009;…”
Section: Empirical Literaturementioning
confidence: 99%
“…Studies by Okiro and Murungi (2018) and Mweni (2014) provide no conclusive evidence on the existing relationship between public debt and economic growth indicating that debt and growth relationships are not a one size fit all, the relation varies from one country to another depending on the country's policies, level of development, and what use the debt amount is subjected to. Similar results are obtained by Lof and Malinen (2013) in an analysis of 20 developed countries for the period 1954-2008 using the VAR model.…”
Section: Empirical Literature On Public Debt and Growthmentioning
confidence: 99%
“…Metode yang digunakan adalah critical review dengan pendekatan penelitian menggunakan evidence-based berdasarkan critical thinking dan bukti yang tersedia. Critical review bertujuan untuk memberi masukan atau rekomendasi secara teoretis dalam kerangka kerja penelitian (Kargbo et al, 2021;Marlina et al, 2019;Murungi & Okiro, 2018;Perry, 2021). Pendekatan evidence-based adalah pendekatan berbasis bukti berdasarkan penelitian sebelumnya untuk memberikan informasi penelitian baru dan menjawab pertanyaan penting secara efektif, efisien, serta mudah diakses (Khalil et al, 2016;Payne et al, 2021;Solinas-Saunders, 2020).…”
Section: Metode Penelitian Metode Analisisunclassified